Religion, Psychiatry, and Psychotherapy: Exploring the Japanese Experience and the Possibility of a Transnational Framework. Issue 2 (1st June 2016) - Harding, Christopher G.
Abstract : This article offers a four-part framework for exploring the complexities and nuances of a modern and contemporary phenomenon in health care and broader public discourse in many parts of the world: the "religion-psy dialogue, " the increasing interchange between the thinkers, leaders, and laypeople of the world's religions and the professionalizing and expanding "psy disciplines"—principally psychiatry, psychology, and psychotherapy. The four parts outlined here—circumstances and orientations, the human person, language, and complementarities and antagonisms—reference the Japanese context in particular but build on experiences elsewhere in the world and are intended to be useful multinationally and transnationally.